2018
DOI: 10.1002/ange.201802238
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Copolymerization as a Strategy to Control the Stability of Self‐Assembled Nanofibers

Abstract: Am ajor challenge in supramolecular polymerization is controlling the stability of the polymers formed, that is,controlling the rate of monomer exchange in the equilibrium between monomer and polymer.T he exchange dynamics of supramolecular polymers based on benzene-1,3,5-tricarboxamide (BTA) can be regulated by copolymerizing molecules with dendronized (dBTA) and linear (nBTA) ethylene glycolbased water-soluble side chains.W hereas nBTAs form long nanofibers in water,dBTAs do not polymerize, forming instead s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…According to the "majority rules" reported for previous supramolecular systems, [18] it seems that the supramolecular polymer or network in this two-component hydrogel system is not formed by the random coassembly of LPF and LPFEG. [16,19] Instead, it appears to be constructed by independent self-association of LPF and LPFEG separately, namely, self-sorting of the chiral assemblies. [7b, 15c] To prove that self-sorting occurs in this two-component hydrogel system, we conducted some control experiments.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…According to the "majority rules" reported for previous supramolecular systems, [18] it seems that the supramolecular polymer or network in this two-component hydrogel system is not formed by the random coassembly of LPF and LPFEG. [16,19] Instead, it appears to be constructed by independent self-association of LPF and LPFEG separately, namely, self-sorting of the chiral assemblies. [7b, 15c] To prove that self-sorting occurs in this two-component hydrogel system, we conducted some control experiments.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However, the interesting issue about this bonding energy spectrum is the fact that supramolecular polymers in which mers are bonded non‐covalently can in principle not only populate the low bonding energy part of the spectrum but also overlap over the entire spectrum depending on the molecular complexity of mers . The monomers of supramolecular polymers investigated so far span a broad range, starting with the simple ones developed initially in which several hydrogen bonds among mers dominate formation of the supramolecular polymer and others where multiple interactions control formation of the polymer . The multiple interactions may involve hydrogen bonding, hydrophobic collapse, π‐orbital overlaps, electrostatics, sterics, metal‐ligand contacts, among other interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, recent reports have shown that the properties of coassembled supramolecular materials can be significantly different than those of the separate components. 11 In this regard, it is crucial to get a comprehensive understanding to which extent the supramolecular interactions in multicomponent systems can direct the properties of soft materials.…”
Section: Introductionmentioning
confidence: 99%